2008
DOI: 10.1186/1471-2458-8-347
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing psychological distress during a disease epidemic: Data from Australia's first outbreak of equine influenza

Abstract: Background: In 2007 Australia experienced its first outbreak of highly infectious equine influenza. Government disease control measures were put in place to control, contain, and eradicate the disease; these measures included movement restrictions and quarantining of properties. This study was conducted to assess the psycho-social impacts of this disease, and this paper reports the prevalence of, and factors influencing, psychological distress during this outbreak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

67
415
6
28

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 480 publications
(516 citation statements)
references
References 20 publications
(30 reference statements)
67
415
6
28
Order By: Relevance
“…The findings are consistent with those from a contemporaneous study assessing the psychosocial impacts of EI, which found that respondents felt that disease control measures were likely to be effective and that they were committed to controlling and eradicating the disease, despite also reporting a range of adverse effects of the outbreak including despair, loss of future hopes, helplessness, isolation, frustration, anger and distress 3 . The positive attitudes were considered likely to have contributed to greater compliance and commitment and to the eventual success of the control measures 3 …”
Section: Discussionsupporting
confidence: 84%
“…The findings are consistent with those from a contemporaneous study assessing the psychosocial impacts of EI, which found that respondents felt that disease control measures were likely to be effective and that they were committed to controlling and eradicating the disease, despite also reporting a range of adverse effects of the outbreak including despair, loss of future hopes, helplessness, isolation, frustration, anger and distress 3 . The positive attitudes were considered likely to have contributed to greater compliance and commitment and to the eventual success of the control measures 3 …”
Section: Discussionsupporting
confidence: 84%
“…So, if associations/societies or non-veterinarian horse professionals, were providing accurate information, then the study findings may imply that managers, who received information from them were more aware and concerned about the disease threat, and hence more engaged. However, the associations with non-veterinarian horse professionals and industry organisations information sources may also be a proxy measure for having experienced more impacts associated with control measures during 2007, such as the cancellation of events and inability to breed horses due to movement restrictions [12,17,19]. Another aspect that could be contributing here is: trusted sources are regarded as the best provider of infection control information [44].…”
Section: Discussionmentioning
confidence: 99%
“…The outbreak lasted five months but during this time it affected more than 70 000 horses, spread over 280 000 square kilometres, and cost the government more than A$350 million before it was successfully controlled and the virus eradicated [10]. The full social and economic impacts of the outbreak are difficult to quantify [11], yet a study conducted during the epidemic found certain groups of horse owners to have much greater psychological distress compared to the general population [12]. Control strategies applied in the outbreak response included horse movement restrictions, emergency vaccination and enhanced on-farm infection control (biosecurity) and public awareness [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A thorough investigation should also be undertaken to understand the social or psychological reasons for under‐reporting. This would enable disease control authorities to better manage future incursions of emerging infectious diseases in Australia, which is very important given that a study reported ‘extremely high levels’ of psychological distress during this outbreak 7 . Anecdotal evidence of under‐reporting is available from several human and animal disease outbreaks worldwide, 1–4 but the psychological or socioeconomic reasons for such behaviour have not been thoroughly investigated, including the under‐reporting of animal diseases in Australia.…”
Section: Proportion Of Under‐reporting In Different Clusters Based Onmentioning
confidence: 99%